International Benchmarking of Prices "A New Pricing Mantra in Industrial Marketing" - Rai, Alok Kumar (Indian Journal of Marketing, 2005)
Pricing has been the most complex marketing decision. In case of Industrial marketing, this decision becomes more complicated, as influencing buyers on the basis of non economic considerations are almost impossible. Post Liberalised era has poured in competition from International giants and the domestic government, in its bid for compliance of WTO obligations and encouraging competition, is deserting the days and policies of protectionism. This has complicated Industrial marketing in India and the most serious victim of this phenomenon has been the prices. Based on the study conducted among Colour Picture Tube Manufacturers and of its users i.e. Colour Television makers, the author feels for a change in pricing methodology and suggests for a new model of pricing i.e. benchmark pricing. This benchmarking domestic prices is against landed price of imported products.